The Regulatory Effects of Paeoniflorin and Its Derivative Paeoniflorin-6′-O-Benzene Sulfonate CP-25 on Inflammation and Immune Diseases - Tu, Jiajie; Guo, Yawei; Hong, Wenming; Fang, Yilong; Han, Dafei; Zhang, Pengying; Wang, Xinming; Körner, Heinrich; Wei, Wei (Frontiers in Pharmacology, 2019)
The plant extract “total glucosides of peony” (TGP) constitutes a mixture of glycosides that is isolated from the roots of the well-known traditional Chinese herb Paeonia lactiflora Pall. Paeoniflorin (Pae) is the most abundant component and and the main biologically active ingredient of TGP. Pharmacologically, Pae exhibits powerful anti-inflammatory and immune regulatory effects in some autoimmune diseases including Rheumatoid Arthritis (RA) and Systemic Lupus Erythematosus (SLE). Recently, we isolated an ester derivative of Pea and modified it with an addition of benzene sulfonate to achieve better bioavailability and higher lipid solubility. This review summarizes the pharmacological activities of Pae and the novel anti-inflammatory and immunomodulatory drug Paeoniflorin-6′-O-benzenesulfonate (CP-25) in various chronic inflammatory and autoimmune disorders. The regulatory effects of Pae and CP-25 make them as promising agents for more related diseases, which is required extensive investigation in the future.